Scottish Shire Elections: Preliminary Findings in Sheriff Court Books1. (October 2015) - MacDonald, Alan
<x xml:space="preserve">Abstract</x> Historians of the Scottish parliament have paid little attention to shire elections because of an apparent lack of local source material. This article explores some of the reasons for this perception and argues that sheriff court records contain considerably more evidence than has been appreciated hitherto. It demonstrates that these records provide details of the electoral process, the regularity of elections, the numbers of electors, external interference in elections and internal divisions within the electorate, local responses to national political events, and attitudes to representation through such things as levying taxes locally to reimburse representatives' expenses. It challenges the once widely‐held view that the lesser nobility, who comprised the electorate, were uninterested in parliamentary participation, suggesting instead that the statute of 1587, by which shire representation was established, was reasonably successful. Finally, it considers the potential for further research in these and other records which, it is argued, will provide a much deeper understanding of 17th‐century Scotland's parliamentary history in particular and political history in general.